Rigid–elastic-thermal coupling dynamics and its application. (7th December 2015) - Song, Haiyan; Hou, Gangling; Sun, Hai; Liang, Lifu
Spacecraft dynamics belongs to rigid–elastic coupling dynamics in general. If thermal stress and thermal effect are further considered, it will cause the more complex rigid–elastic-thermal coupling dynamics. For the aforementioned kind of coupling dynamics, it is difficult to establish the basic equations directly. It has proved that a suitable way to study complex coupling problems is by work–energy theorem and the law of conversation of energy. Using the energy method, Hamilton principle of rigid–elastic-thermal coupling dynamics is established. The stationary value conditions of Hamilton principle of rigid–elastic-thermal coupling dynamics are derived. The physical meaning of the stationary value conditions is indicated. As an application of rigid–elastic-thermal coupling dynamics, the actual example of spacecraft is given to reveal that there existed thermal stiffening or softening problems in rigid–elastic-thermal coupling dynamics, just like dynamic hardening or softening problems in spacecraft dynamics.